Mid-term assessment of subtalar arthroereisis with Talar-Fit implant in pediatric patients with flexible flatfoot and comparing the difference between different sizes and exploring the position of the inserted implant - Xie, Huan-guang; Chen, Li; Geng, Xiang; Wang, Chen; Zhang, Chao; Wang, Xu; Huang, JiaZhang; Ma, Xin (Frontiers in Pediatrics, 2023)
Background Subtalar arthroereisis (STA) has gained growing acceptance as a viable approach solution for the management of pediatric flexible flatfoot. However, STA still remains controversial. The purpose of this study is to assess the effect of STA using the Talar-Fit implant for treating pediatric flexible flatfoot. Specifically, the aims of the study are as follows: first, to present the mid-term outcomes of STA using the Talar-Fit implant; second, to compare the radiographic and clinical outcomes associated with varying sizes of Talar-Fit implant; and third, to analyze the optimal position of the inserted implants. Methods A retrospective analysis was conducted on a cohort of 57 pediatric patients diagnosed with flexible flatfoot (77 feet) who underwent STA utilizing Talar-Fit between January 2014 and December 2021. The participants were categorized into five groups according to the size of the implant: Group 8, Group 9, Group 10, Group 11, and Group 12. The evaluation included the assessment of clinical function using the American Orthopaedic Foot and Ankle Society (AOFAS) ankle–hind foot score, as well as the assessment of radiographic data such as the calcaneal pitch angle (CPA), lateral Meary angle (LMA), talar declination angle (TDA), and medial longitudinal arch angle (MLAA) were evaluated. Furthermore, the position of the inserted implants was also recorded, including angle, depth, and distance. The comparison of pre- and postoperation was conducted using the paired Student's t-test, whereas the analysis of differences among subgroups was performed using the Wilcoxon rank-sum test. A P-value < 0.05 is considered statistically significant. Results In total, 57 pediatric patients (77 feet) were successfully followed-up for an average period of 26.8 months. The overall AOFAS score significantly improved from 58.6 ± 10.9 to 85.2 ± 8.6 (P < 0.001). Furthermore, the LMA decreased from 20.3° ± 3.6° to 4.5° ± 1.3°, the CPA increased from 14.8° ± 1.6° to 23.6° ± 2.7°(P < 0.05), the TDA decreased from 40.2° ± 2.3° to 25.5° ± 3.2°(P < 0.05), and the MLAA decreased from 140.1° ± 2.8° to 121.4° ± 3.9°(P < 0.05). No statistically significant differences were observed among subgroups regarding the final outcomes. The improvements of CPA, TDA, and MLAA among different groups were significantly different; however, the adjusted P-values were all greater than 0.05. The implant were inserted at a mean angle of 89.5° ± 2.4°, a mean depth of 0.9 mm ± 2.1 mm, and a mean distance of 9.9 mm ± 0.9 mm. Eight patients experienced complications, including six cases of pain occurrence and two cases of implant dislocation. Conclusion STA with Talar-Fit has demonstrated satisfactory mid-term outcomes. A Talar-Fit with a larger size may demonstrate a superior effect when compared with that of a smaller size. The implants were inserted in a similar position, indicating that the medial edge of the implant may be possible to transcend the midline of the talus neck.